Excombatientes: ¿germen de guerras civiles? - Ángel Alcalde (Amnis)
This article explores the hypothesis that demobilized ex-combatants can constitute a conflictive group, which might aggravate social tensions, leading to civil war situations. For this purpose, the article examines the European interwar period, and the history of the First World War veterans. Firstly, the article assesses the historiography linked to the « brutalization » theory. Secondly, studies on the processes of disarmament, demobilization and reintegration of ex-combatants (DDR), a perspective proposed by social and political scientists, is applied to the study of the interwar period. The article concludes that a comparative history of DDR might be useful to overcome the contradictions of the « brutalization » theory.